Feeding practices and obstetricians recommendations during COVID-19: a telephone-based qualitative study in South India - Sucharitha, Sree T.; Lakshmi, R. Vijaya; Venugopal, R.; Rajasingh, Revathi; Nivetha, R. (International Journal Of Community Medicine And Public Health, 2024)
Infant and young child feeding practice (IYCF) by World Health Organization (WHO) strongly encourage initiation and continuation of exclusive breastfeeding (EBF) in the COVID-19 pandemic backdrop with essential counseling about the benefits of breastfeeding against risks of transmission. This study aimed to explore qualitatively the knowledge and understand the recommended practices regarding infant and IYCFs during COVID-19 pandemic among obstetricians in diverse care settings in Chennai. One-to-One telephone-interviews were conducted among sixteen obstetric practitioners from diverse care settings in Chennai during May 2021-October 2021 using a 13-item interview guide and recorded with informed consent. The transcribed data were analyzed thematically. Among the all-female study participants, the mean age was 39.7 years (SD=10.45 years) and 68.8% (11) were aged 31-40 years, 180 lactating mothers received COVID-19 counseling and 130 referred for testing in preceding month, 56.3% were aware that COVID- 19 is not passed in breast milk and 93.8% knew it is safe to feed breast milk from suspected or confirmed positive mothers. All obstetricians were aware of hygiene recommendations for lactation mothers and only 75% were aware of WHO recommendation for IYCF during-COVID-19. This qualitative study unearths the key areas to focus on during awareness and training sessions for obstetricians further strengthen the promotion of optimal breastfeeding practices during the COVID-19 pandemic.